The Influence of Personal Selling and Telemarketing on Sales Volume of Container Export Services: Case Study in the General Agency Division of PT Samudera Agencies Indonesia Surabaya Branch - Alfina Rahma Nazilal Mubarok; R. Yuniardi Rusdianto (Formosa Journal of Multidisciplinary Research, 2024)
The growth of exports by sea shows an increase in export sales volume in Indonesia. A leading local company in Indonesia, PT. Samudera Indonesia, widely known in the export and import industry. This study aims to identify and know about the Effect of Personal Selling and Telemarketing on the Sales Volume of Container Export Services in the General Agency Division of PT Samudera Agencies Indonesia Surabaya Branch. This research method is quantitative descriptive. The results of this study are Personal Selling and Telemarketing have a significant positive effect on the Sales Volume of Container Export Services, Personal Selling variables have a significant positive effect on the Sales Volume of Container Export Services, Telemarketing variables have a significant positive effect on the Sales Volume of Container Export Services.